Adjective Word and Phrase in Meaning Elaboration Repertoire of Sportainment News - Puspitasari, Indah; Amri, Taufiq (Universitas Muria Kudus, 2022)
Penelitian ini memiliki tujuan untuk mengetahui kata sifat dan frase dalam repertoar perluasan makna berita sportaiment. Metode yang digunakan dalam penelitian ini adalah metode simak. Hal tersebut karena data informasi pada penelitian ini secara langsung bersumber dari hasil penyimakan (wacana berita utama Sportainment koran Jawa Pos ). Dari metode tersebut, teknik yang digunakan adalah teknik baca-catat. Teknik baca dilakukan dengan cara membaca secara cermat dan teliti semua hal yang mempunyai ciri sebagai bentuk perluasan makna, selanjutnya kegiatan pencatatan. Bentuk perluasan makna yang terdapat pada wacana berita utama Sportainment koran Jawa Pos berupa kata sifat dan frase. Penggolongan bentuk perluasan makna tersebut didasarkan pada perluasan makna yang terkandung dalam kata yang ditemukan pada data. Bentuk perluasan makna yang ditemukan pada wacana berita utama Sportainment koran Jawa Pos cukup banyak, hal ini menandakan perluasannya bersifat objektif. This study aims to determine the adjectives and phrases in the repertoire of expanding the meaning of sports news. The method used in this research is the referential method. This is because the information data in this research is directly sourced from the results of listening (the main news discourse on the Jawa Pos newspaper Sportainment). From this method, the technique used is the reading-note technique. Reading technique is done by reading carefully and thoroughly all things that have characteristics as a form of expansion of meaning, then recording activities. The form of expansion of meaning in the form of words was found in many different word classes, namely nouns (nouns) found a total of 121 data, verbs (verbs) found a total of 139 data, and adjectives (adjectives) found a total of 64 data, while the form of meaning expansion in the form of phrases, namely noun phrases found a total of 38 data, work phrases found a total of 34 data, and adjective phrases found a total of 9 data. Taste value includes 142 data of pejorative assessment and 263 data of ameliorative assessment. The assessment depends on each language community concerned. The function of expanding meaning as a metaphor designation in this study found as many as 359 data, while the function of expanding meaning as indicating metonymy in this study found as many as 11 data, and the function of expansion of meaning as an ellipsis designation in this study found as many as 35 data.